Emerging Role of Hepatic Ketogenesis in Fatty Liver Disease - Mooli, Raja Gopal Reddy; Ramakrishnan, Sadeesh K. (Frontiers in Physiology, 2022)
Non-alcoholic fatty liver disease (NAFLD), the most common chronic liver diseases, arise from non-alcoholic fatty liver (NAFL) characterized by excessive fat accumulation as triglycerides. Although NAFL is benign, it could progress to non-alcoholic steatohepatitis (NASH) manifested with inflammation, hepatocyte damage and fibrosis. A subset of NASH patients develops end-stage liver diseases such as cirrhosis and hepatocellular carcinoma. The pathogenesis of NAFLD is highly complex and strongly associated with perturbations in lipid and glucose metabolism. Lipid disposal pathways, in particular, impairment in condensation of acetyl-CoA derived from β-oxidation into ketogenic pathway strongly influence the hepatic lipid loads and glucose metabolism. Current evidence suggests that ketogenesis dispose up to two-thirds of the lipids entering the liver, and its dysregulation significantly contribute to the NAFLD pathogenesis. Moreover, ketone body administration in mice and humans shows a significant improvement in NAFLD. This review focuses on hepatic ketogenesis and its role in NAFLD pathogenesis. We review the possible mechanisms through which impaired hepatic ketogenesis may promote NAFLD progression. Finally, the review sheds light on the therapeutic implications of a ketogenic diet in NAFLD.